2006
DOI: 10.1128/aem.01097-06
|View full text |Cite
|
Sign up to set email alerts
|

Global Gene Expression Analysis of Yeast Cells during Sake Brewing

Abstract: During the brewing of Japanese sake, Saccharomyces cerevisiae cells produce a high concentration of ethanol compared with other ethanol fermentation methods. We analyzed the gene expression profiles of yeast cells during sake brewing using DNA microarray analysis. This analysis revealed some characteristics of yeast gene expression during sake brewing and provided a scaffold for a molecular level understanding of the sake brewing process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
60
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 29 publications
3
60
0
1
Order By: Relevance
“…Vitamin B1 forms the cofactor thiamin pyrophosphate, which is essential for sugar utilization by S. cerevisiae, in particular for sugar fermentation (Bataillon et al 1996;Hohmann and Meacock 1998;Mojzita and Hohmann 2006). Indeed, several reports have shown significant up-regulation of thiamin metabolism genes in fermenting yeast cells in various industrial settings including wine, sake, and bread dough (Rossignol et al 2003;Tanaka et al 2006;Wu et al 2006), and in yeast cells cultivated in sugarcane molasses (Shima et al 2005), indicating that there is a high demand for thiamin (and its precursors) under these industrial conditions. However, it is well known that for S. cerevisiae, as well as for other members of the Saccharomyces sensu stricto complex, the presence of thiamin in the medium has a negative effect on the initial growth phase of the yeast cells, although it does not affect the final cell density (Minami et al 1982;Nakamura et al 1982;Kamihara and Nakamura 1984).…”
Section: Phenotypic Consequence Of the Amplified Sno/snz Genesmentioning
confidence: 99%
“…Vitamin B1 forms the cofactor thiamin pyrophosphate, which is essential for sugar utilization by S. cerevisiae, in particular for sugar fermentation (Bataillon et al 1996;Hohmann and Meacock 1998;Mojzita and Hohmann 2006). Indeed, several reports have shown significant up-regulation of thiamin metabolism genes in fermenting yeast cells in various industrial settings including wine, sake, and bread dough (Rossignol et al 2003;Tanaka et al 2006;Wu et al 2006), and in yeast cells cultivated in sugarcane molasses (Shima et al 2005), indicating that there is a high demand for thiamin (and its precursors) under these industrial conditions. However, it is well known that for S. cerevisiae, as well as for other members of the Saccharomyces sensu stricto complex, the presence of thiamin in the medium has a negative effect on the initial growth phase of the yeast cells, although it does not affect the final cell density (Minami et al 1982;Nakamura et al 1982;Kamihara and Nakamura 1984).…”
Section: Phenotypic Consequence Of the Amplified Sno/snz Genesmentioning
confidence: 99%
“…Accumulation of ergosterol and trehalose was reported to exert protective effect against various stresses that yeast cells suffered (Cot et al, 2007;Hincha et al, 2002;Lei et al, 2007;Pham and Wright, 2008;Wu et al, 2006). The biosynthesis of trehalose and ergosterol was affected by the size of yeast flocs and zinc supplementation under VHC fermentation conditions in which the yeast flocs suffered more severe stresses, demonstrating the possibility to develop process engineering strategies to improve the performance of the fermentation system.…”
Section: Impact On Cell Viability and Biosynthesis Of Intracellular Tmentioning
confidence: 99%
“…In order to elucidate the molecular mechanisms responsible for the excellent fermentation properties of modern sake yeast strains, gene expression profiling has been used to identify the relevant genes and pathways (31,39,44). For example, our recent analyses revealed that the stress-responsive transcription factors Msn2p and Msn4p (Msn2/4p) (19,30) and Hsf1p (32) are significantly inactivated in modern sake yeast cells during fermentation (22,39).…”
mentioning
confidence: 99%